2020
DOI: 10.14569/ijacsa.2020.0110774
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Homomorphic Encryption and Address of New Trend

Abstract: Encryption is the process of disguising text to ensure the confidentiality of data transmitted from one party to another. Homomorphic encryption is one of the most important encryption-related processes which allows performing operation over encrypted data. Using different public key algorithms, homomorphic encryption can be implemented in any scheme. There are many encryption algorithms to secure operations and data storage, which after calculations can obtain the same results. While there is a considerable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Homomorphic encryption enables computations to be performed on encrypted data without decrypting it first, preserving privacy throughout the computation process (Hamza, et al, 2022;Alharbi, et al, 2020). It allows for operations such as addition and multiplication to be performed on ciphertexts, producing encrypted results.…”
Section: Privacy-enhancing Technologies (Pets): a Reviewmentioning
confidence: 99%
“…Homomorphic encryption enables computations to be performed on encrypted data without decrypting it first, preserving privacy throughout the computation process (Hamza, et al, 2022;Alharbi, et al, 2020). It allows for operations such as addition and multiplication to be performed on ciphertexts, producing encrypted results.…”
Section: Privacy-enhancing Technologies (Pets): a Reviewmentioning
confidence: 99%
“…Achievements: The authors of this paper suggested a way to secure the data from breach by simply removing the user's information from the system completely. Alharbi et al [29] introduced a literature survey related to the HE algorithm. Techniques used: The survey aims to reduce the gap between the algorithm and its applications in terms of providing security.…”
Section: Related Workmentioning
confidence: 99%
“…Homomorphic encryption is based on mathematical algorithms that enable operations on encrypted data, such as addition and multiplication, to produce encrypted results that can be decrypted to give the same output as if the operations had been performed on the original unencrypted data. This means that data can be processed without ever being revealed in its unencrypted form, providing a higher level of security and privacy [9]. Homomorphic encryption aids in thwarting risks like data leaks when in use and when the data is at rest [68].…”
Section: Encryption and Key Management In The Cloudmentioning
confidence: 99%